Penguin guano suppresses the grazing rate and modifies swimming behavior in Antarctic Krill (Euphausia superba) - Hellessey, Nicole; Weissburg, Marc; Fields, David M. (Frontiers in Marine Science, 2025)
Antarctic krill (Euphausia superba) are a key component of the Antarctic ecosystem linking primary and some secondary production to higher trophic levels including fish, penguins, seals, and whales. Understanding their response to environmental stimuli therefore provides insights into the trophic ecology of Antarctic systems. This laboratory study quantified the influence of penguin guano, a presumptive predator cue, chlorophyll concentration and flow speed on krill swimming behavior. In addition, ingestion rates with and without guano were measured. Such inquiries are necessary to determine if predator risk cues modify krill activities in ways that have consequences for other members of the Antarctic trophic web. Krill often exhibited acute turns when guano was present and varied their swimming speeds more when guano was present. These are both indicators of avoidance behavior to the negative chemical cues represented by penguin guano. Similarly, krill’s ingestion rates dropped significantly for a prolonged period of time in the presence of guano. This decrease in feeding will have impacts on krill’s nutritional value to their predators, prey uptake rates (prey survival) and the sequestration of carbon to the deep ocean as krill decrease their defecation rates. This study supports the hypothesis that krill use chemical signals to detect and behaviorally respond to food and predation risk.